HUKUM ISLAM: ANTARA TEKS, MORAL, DAN AKAL (Mazahib, 2007)
The development of paradigm of modern scientific has a significant impact on the development of jurisprudence. A case in point is the influence of postmodernism which has led to a thought that law is no longer deemed as merely a social reality; instead, law is also a metaphysical reality. The shift of jurisprudence paradigm from positivism to postmodernism is considered in line with Islamic thoughts on jurisprudence. This is because: first, Islamic jurisprudence requires the combination of mind and heart; second, the shortcoming of bayani, `irfani and burhani epistemology necessitates a par excellence epistemology i.e. their combination; third, religious morality plays an important role in forming a social order.